Value of operational experiment in the investigation of crimes involving bribery - Шмигельський, Віктор Валентинович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article defined the legal nature of the use by units of the operative experiment to achieve the objectives of the disclosure of crimes related to bribery by the employes of operatively search subdivivisions. Determined that the method of experiment creates the possibility of overcoming in the legislation criminal responsibility for provocation of bribes.